Behind Bars, Beyond Vision: A Study on Ocular Morbidity in Morang District Jail, Nepal. - Sah, Ruchika; Pokharel, Subash; Sah, Manish; Yadav, Rajesh (Optometry & Visual Performance, 2025)
Background: To investigate the frequency and forms of ocular morbidity among detainees in Morang District Jail, Nepal, and to document the underlying causes of these disorders. Method: The cross-sectional study was carried out in the Morang District Jail in Nepal. The study population consisted of all convicts who were incarcerated throughout the research period. A systematic questionnaire was used to acquire demographic information and ocular health history, followed by a thorough ocular examination done by a professional ophthalmologist, optometrist, and ophthalmic assistant. The examinations included visual acuity tests, refraction, slit-lamp assessments, and fundus examination. Results: The research involved 941 convicts, 838 (89.05%) male and 103 (10.95%) female. The inmates ranged in age from 19 to 78 years, with an average age of 35.41 ± 11.02 years and a 51.75% frequency of ocular morbidity. The most prevalent ocular morbidity was refractive error (28.13%), followed by presbyopia (25.87%), cataract (7.39%), dry eye (6.98%), and allergic conjunctivitis (4.93%). Conclusion: Inmates were found to have a significant frequency of ocular morbidity. Refractive error was the leading cause of ocular mor